NGHIÊN CỨU MỘT SỐ CHỈ TIÊU SINH SẢN VÀ SINH TRƯỞNG CỦA CHUỘT NHẮT TRẮNG Mlac:ICR NUÔI TẠI VIỆT NAM - Nguyễn, Chí Hiếu; Mẫn, Thị Thành; Hoàng, Trung Hưng; Nguyễn, Đăng Khuê; Trần, Thị Hương Thơm; Trần, Thị Hồng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
REPRODUCTIVE AND GROWTH INDICATORS OF Mlac:ICR MICE IN VIETNAM This study was conducted on 10 lots with 2800 females and 1400 males of reproductive Mlac:ICR mice; 199 male and 200 female pups raised at the National Institute for Control of Vaccine and Biologicals from June to December 2020 in a closed system facility with controlled environmental factors to evaluate the pregnant, litter size, number of quality weaned pups; growth rate from birth to 5 weeks of age. The results showed that rate of pregnant mice in coupling lots ranging from 70.7% to 78.6%; Average of success birth rated 99.1% of the total pregnancy; Number of new born mice was from 2 to 20 head per litter; mean was 11.6; Weaning mice ranged from 6.3-7.1 heads/ litter (mean is 6.7 heads/litter); The weight of newborn pups averaged 1.78g (between 1.48-2.1g). In the first 3 weeks, average weight gain of mice was 0.54g per day, after weaning between 21 to 35 day of age the average weight gain was 1.05g per day, it was higher in male than in female, especially in the post-weaning period, male mice reached 1.15g/day while female was 0.95g/day. The average weight of female mice obtained after lactation reached 12.93g and 13.43g for male mice. After weaning, mice gained weight, equivalent to the original breed; The weight is completely in accordance with the age and weight standards for control quality testing of vaccines and biological.